Parâmetros Físicos do Movimento em Libras: um estudo sobre intensificadores - Rosana Passos (2014)
The present study assays the movement in Libras according to a dynamic and complex perspective in order to analyze which physical parameters of the movement express, in degrees, the grammatical intensity in Libras. The adopted methodology combines phonological theories in sign languages with experimental evidences through technology and from studies that have explored the kinematics of movement. An experiment was carried out with three hearing subjects, users of Libras as second language (L2), making use of visual stimuli at three levels of intensity. Moreover, the production in Libras was taped and the FlowAnalyzer tool was utilized to extract the physical parameters of the movement, among which were selected: duration, energy, variance and mean velocity. The examination of such data was performed by statistical analysis ANOVA. The initial proposition considered in the formulation of this thesis was that the degrees of grammatical intensity would be increased as the levels of the stimuli were raised (level 1 <level 2 <level 3), as well as there would be an increase in the values of the physical parameters related to the Movement in Libras: (degree 3> degree 2> degree 1). It was verified that the duration is an important grammatical correlate to express the different degrees of intensity in Libras. It influenced somehow other physical parameters which implied changes in the movement in Libras in a non-linear way, disproportionate to the cause, as predicted by the Dynamic and Complex Systems modeling. Time (in this study represented by duration) is crucial for the development of a Dynamic and Complex System, such as Libras, but an isolated factor is not deterministic to express grammatical organization in languages. Similarly, the mean velocity is relevant to the grammatical intensification system in Libras. The results indicate that the mean velocity followed this thesis prediction that as the intensity levels of the stimuli increased, the degrees of grammatical intensity in Libras would be increased. Based on the results, it is possible to suggest that the movement in Libras should be understood complex and dynamically. Furthermore, the expression of the different degrees of grammatical intensity in Libras signaling would have emerged with the self-organization of movement variables as a result of this interaction and influence between factors (intensity, subject and stimuli) and variables (duration, energy, variance and mean velocity). The stimuli presented to the users of Libras were also exposed to three non-signaling hearing, speakers of Brazilian Portuguese (PB), called control group, with the objective of ascertaining the alternation in the use of the operators of grammatical intensity in PB speakers as a control group. The results indicate that the different levels of intensity of the stimuli cause a variability in the expression of the different degrees of grammatical intensity. Although there were variations in the subjects' grammatical choices regarding the use of PB intensity operators, there was a tendency for the participants to opt for the use of free morphemes, indefinite intensifier and comparative intensifiers, in addition to unanimously dispensing the bound morpheme.